Incorporating Capacity Building as a Pathway to Environmental Stewardship for Public Schools in Kenya - Charles N. Kariuki; Bessy E. Kathambi; Justus O. Inyega (CV. Literasi Indonesia, 2023)
Education has been touted as a major driver toward the achievement of Sustainable Development Goals (SDGs). However, environmental stewardship takes a peripheral position in the pre-service and in-service training of teachers. As a result, most teachers and school heads that are supposed to champion stewardship activities in schools remain poorly equipped to undertake such activities. More so, a review of the literature finds glaring gaps in research in that most studies have only concentrated on student performance, teacher-student ratio, student discipline, etc. This study, therefore, sought to survey to establish the rationale for incorporating capacity building as a pathway to environmental stewardship in public schools in Kenya. The study sampled 260 public school teachers in the Githunguri Sub-county of Kiambu County in Kenya. Data from the teachers was collected using a structured questionnaire while 15 principals were also interviewed. Secondary data was collected through desktop reviews. The study established that the majority of the teachers had neither received pre-service (88.8%) nor in-service (90.4%) training on issues around environmental stewardship. A correlational analysis also established positive linear associations for capacity building, leadership roles, and stewardship activities (R = 0,803) and (R = 0,874) respectively. As a consequence, this hampered stewardship activities in schools within the study locality. For instance, the study established that most of the schools did not have a proper waste management system (88.1%) or even an environmental policy (75%). This study will inspire policy frameworks for future training of teachers to ensure that Kenya meets her SDG targets.